Development of a Gamified Website Using the Rapid Application Development (RAD) Method for Computational Thinking Elements in Vocational High Schools - Latifah, Luluk; Wijanarko, Dwi; Anis, Samsudin (Universitas Negeri Semarang, 2023)
The competency in computational thinking elements among students at SMK Al-Musyawirin is still lacking. The learning outcomes, averaging 75, are below the minimum passing criteria. Currently, the teaching method relies solely on textbooks, resulting in insufficient understanding of the material by the students. To address this issue, there is a need for an educational medium that can enhance students comprehension of the subject matter, such as a website. This study aims to develop a gamified website as a learning medium to improve students understanding of computational thinking elements. The website was developed using the Rapid Application Development (RAD) method, which involves stages of requirements planning, RAD design workshop, and implementation. The instruments used were: (1) black-box questionnaire; (2) material feasibility questionnaire; (3) User Acceptance Testing questionnaire; and (4) objective tests. The validity of the instruments was calculated using CVR, while their reliability was measured using Cronbach's Alpha, ICC, and Spearman-Brown. Finally, test reliability was assessed using the Spearman-Brown formula. Data analysis employed categorical analysis for media and material feasibility, as well as user acceptance levels. The effectiveness of the website was measured using N-Gain and t-tests. Results indicated that the website is feasible in terms of media and material, well-received by students, and effective and significant in improving computational thinking competencies, particularly in the conversion between number systems (binary, decimal, hexadecimal).